Harnessing Nutrients From Seawater For Plant Requirment - M PRAMA YUFDY (Indonesian Center for Agriculture Land Resource Development, 2008)
Numerous research findings have informed that nutrients for plant requirement can be explored from seawater. Apart of its high salinity, seawater contain high amount of cations. Efforts have been done to produce K fertilizer from seawater. In some countries, seawater based agriculture has also developed. Though, sodium concentration is very high in seawater, it is known as a beneficial nutrient to plant, and in some cases it can replace part of K function. Numerous research findings have shown that Na is essential for non-halophyte crops such as rice and tomato. Sodium is also essential for many crassulacean acid metabolism (CAM) species. Since pineapple is classified as CAM species, it has proven in a study indicated that some of K requirement can be substituted by Na from seawater when it was applied in diluted solution. Thirty percent of K fertilizer substitution by Na from seawater plus 70% K from KCl for pineapple can play the role of 100% K (300 kg/ha) for production of fruit fresh weight, without having any negative effects on the soil and plant. To make seawater worth pursuing for nutrients source, it needs to identify the potential crops that tolerant to salinity and the potential crops that require Na as nutrient as well as to partially substitute K. The opportunity is very high in Indonesia since the country has very large agricultural areas located close to the sea.